Ethnobotanical survey on anti-tuberculosis plants in Mbujimayi, Democratic Republic of the Congo - Malangu Lambert Muamba; Kitambala Marsi Mbayo; Numbi Evodie Wa Ilunga; Ilunga Eddy Mbuyu; Kabeya Justin Kanda; Otete François Dikala; Ebalantshim Daniel Munakongo; Mwinensenge James Maloba; Nonga Welcome Muyumba; Kalonji Serge Mbuyi; Muya Richard Kalunga; Tsheko Manya; et al. (Orapuh Journal)
Introduction